2009
DOI: 10.1186/bf03352985
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear thermoremanence corrections for Thellier paleointensity experiments on single plagioclase crystals with exsolved magnetites: a case study for the Cretaceous Normal Superchron

Abstract: Single plagioclase paleointensity experiment has been an excellent tool to reliably estimate ancient geomagnetic field intensity. Although transparent plagioclases with magmatic nanophase magnetites have shown their potential for paleointensity estimation, in most cloudy plagioclases with exsolved magnetites, the problems of strong anisotropy as rod-shape magnetites, the hyperbolic tangential saturation of thermoremanence (TRM), and slow cooling of host plutons need to be addressed. In this paper, we propose e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In some plutonic and metamorphic rocks, silicate minerals such as plagioclase and pyroxene contain tiny rods of exsolved magnetite [e.g., Evans and McElhinny , ; Evans et al ., ; Hargraves and Young , ; Fleet et al ., ; Davies , ; Wenk et al ., ]. Plagioclase and pyroxene containing exsolved magnetite has relatively strong magnetizations so that single crystals can be routinely measured in currently available rock magnetometers [ Renne et al ., ; Usui and Nakamura , ]. In addition, silicate crystals with exsolved magnetite show high magnetic stability with SD‐like characteristics [ Renne et al ., ; Feinberg et al ., ; Muxworthy and Evans , ], including ideal (linear) behavior in Thellier‐type paleointensity experiments [ Dunlop et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some plutonic and metamorphic rocks, silicate minerals such as plagioclase and pyroxene contain tiny rods of exsolved magnetite [e.g., Evans and McElhinny , ; Evans et al ., ; Hargraves and Young , ; Fleet et al ., ; Davies , ; Wenk et al ., ]. Plagioclase and pyroxene containing exsolved magnetite has relatively strong magnetizations so that single crystals can be routinely measured in currently available rock magnetometers [ Renne et al ., ; Usui and Nakamura , ]. In addition, silicate crystals with exsolved magnetite show high magnetic stability with SD‐like characteristics [ Renne et al ., ; Feinberg et al ., ; Muxworthy and Evans , ], including ideal (linear) behavior in Thellier‐type paleointensity experiments [ Dunlop et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Using the directional dependence of magnetic hysteresis properties, Gee and Meurer [] inferred strong preferred orientation of exsolved magnetites within clinopyroxene crystals from oceanic gabbros. The remanence anisotropy tensors were determined for orthopyroxene [ Lagroix and Borradaile , ; Selkin et al ., ] and plagioclase single crystals [ Usui and Nakamura , ; Selkin et al ., ] using anhysteretic remanent magnetization (ARM). These studies reported extremely high remanence anisotropy ( Pj=235, where P j is the Jelinek [] anisotropy degree).…”
Section: Introductionmentioning
confidence: 99%
“…However, the strong texture of such a magnetite within a host mineral produces a large magnetic anisotropy (Feinberg et al, 2006). This makes paleointensity experiments using single silicate crystals difficult when they contain exsolved magnetite (Usui and Nakamura, 2009), whilst a nearrandom texture of host minerals would reduce the magnetic anisotropy at a whole rock scale (Usui et al, 2006). If one uses whole rock samples, it is necessary to discriminate samples whose magnetic signals are dominated by secondary magnetic minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a possibility that NRM of exsolved magnetite is a thermochemical remanent magnetization (TCRM) rather than a TRM since the formation temperature of exsolved magnetite in plagioclase is not clear (Feinberg et al 2005). In that case, obtained paleointensity could give the lower limit of the field strength at the age, as TCRM acquisition is less efficient than TRM acquisition (Stacey and Banerjee 1974;Usui and Nakamura 2009). Wakabayashi et al (2006) and Tsunakawa et al (2009) predicted that most of the stable remanence of the Iritono granite was carried by magnetite inclusions in plagioclase.…”
Section: Anisotropy Effect On Paleointensitymentioning
confidence: 99%
“…Plagioclase with exsolved magnetite is potentially an excellent recording medium of the ancient geomagnetic field, but should be treated carefully because (1) magnetic remanence anisotropy caused by needle-shaped magnetite can affect paleomagnetic results (Paterson 2013;Usui et al 2015), (2) nonlinear thermoremanence acquisition (Selkin et al 2007), and (3) unknown formation temperature of exsolved magnetite (Feinberg et al 2005). Usui and Nakamura (2009) reported paleointensity using single plagioclase crystals separated from a granitic rock, although they did not claim they achieved exact, reliable estimates. Despite its potential for establishing the long-term trend of the geomagnetic field strength, paleointensity of single crystals separated from plutonic rocks have not been compared to that of the host whole rock to assess its reliability.…”
Section: Introductionmentioning
confidence: 99%